The Long-Term Effects of Government Deficits on the U.S. Output Potential - von Furstenberg, George M. (Journal of Finance, 1978)
George M. von Furstenberg, The Long-Term Effects of Government Deficits on the U.S. Output Potential, The Journal of Finance, Vol. 33, No. 3, Papers and Proceedings of the Thirty-Sixth Annual Meeting American Finance Association, New York City December 28-30, 1977 (Jun., 1978), pp. 989-1001